Numerical Simulation of a No-Insulation BSCCO Toroidal Magnet Applied in Magnetic Confinement Fusion - Yi Zhang; Yuejin Tang; Ying Xu; Zhong Xia; Li Ren (Science and Technology of Nuclear Installations)
At present, the Tokamak has become a mainstream form of the magnetic confinement fusion device. The toroidal field (TF) magnet in the Tokamak system is required to generate a high-steady field to confine and shape the high temperature plasma. To secure high current density and high thermal stability, the no-insulation (NI) winding technique is used in the fabrication of the TF magnet. During plasma operation, heat is generated in the TF magnet caused by the interaction with central solenoid (CS) coils, poloidal field (PF) coils, and the plasma current. The heat generated in NI coils is complex owing to the existence of current flow between adjacent turns. Thus, it is necessary to calculate the thermal problems. Taking into consideration the effect of turn-to-turn contact resistance, this paper presents the thermal behavior of a NI toroidal magnet under different operating conditions. The NI toroidal magnet is composed of 10 double-pancake (DP) coils wound with BSCCO tapes. The analysis procedure combines the finite element method (FEM) with an equivalent circuit model. This analysis has applicability and practical directive to the design of cryogenic cooling system for NI toroidal magnet.